Medication errors in nursing students - Zahra Khalili; Mehdi Molavi Vardanjani; Morteza Shamsizadeh; Neda Alimohammadi; Shahin Tohidi; Gholamhosein Fallahinia; Leili Tapak (Kurdistan University of Medical Sciences, 2018)
Background & Aim: Internship nursing students are at risk of making medication errors due to their independence in practice. In order to protect the patient, identification of a drug error is necessary. The purpose of this study was to investigate the pharmacological errors of interns nursing students in the field. Materials & Methods: This descriptive study was conducted on 87 undergraduate nursing students in Hamedan Nursing and Midwifery Faculty, who had not completed their period of study. The data were collected using a questionnaire containing demographic information and error probability (33 items) based on a 5-degree Likert scale (from very low to very high). The analysis was done using descriptive and inferential statistics. Results: Most of the students were 23.24 ± 1.69 years old and had a mean score of 16.06±0.99. The most likely occurrence of errors in intern nursing students was in the field of multi-drug infusion in both cases regardless of medication interactions and giving the medication by wrong number. Conclusion: The results of this study showed that there was a risk of medication errors in nursing students. Therefore, educational authorities should use strategies to prevent medication errors in their training program.